Analysis of the Water Quality of the Iwan River in Darmaji Village, Kopang District, Central Lombok Regency - Umbu, Yohanis; Melinda, Tina; Majdi, Muhamad (Jurnal Pijar Mipa, 2025)
The Iwan River is one of the rivers in Darmaji Village, Kopang District, Central Lombok Regency. People often use This river for daily life, washing, bathing and irrigating rice fields. People also throw household waste into river water bodies. This hamlet does not yet have clean water and a PDAM network. This research uses the pollution index method to determine the water quality of the Iwan River in Darmaji Village and the water quality status of the Iwan River in Darmaji Village. The research method used is quantitative research with an experimental approach according to Government Regulation Number 22 of 2021 and Water Quality Status with the Pollution Index. Based on the results of the Iwan River water quality, it is still below quality standards, so it is still safe for washing and agricultural activities; namely, in upstream samples, there are TSS results of 0.724 mg/L, temperature 26.8, pH 7, BOD 0.5 mg/L, COD 8 mg/L, oil and fat 1.518 mg/L and total Coliform 24000 MPN/ml while the middle sample had TSS results of 1.574mg/L, Temperature 26.7, pH 6, BOD 1.1mg/L, COD 4mg/L, oil and fat 0.066 mg/L, and total Coliform 930 MPN/ml. In downstream samples, there were TSS results of 1.68 mg/L, Temperature 26.8, pH 7, BOD 0.5 mg/L, COD 12mg/L, oil and fat 0.108mg/L and total Coliform 230MPN/ml and Based on the Pollution Index calculation results, the Iwan River is polluted (lightly polluted) but still safe to use for agriculture.